Utilization Of Sengon Wood Sawdust Waste as Esterified Cellulose-Based Bioadsorbent for CD(II) Wastewater Purification - Rizky Fauzan; Nisa Rahmah Mujahidah; Teguh Aditya Nugraha; Nasya Azzahra; Tifa Paramitha; Bambang Soeswanto; Rony Pasonang Sihombing (Journal of Green Science and Technology, 2025)
Cadmium (Cd) is a heavy metal with high toxicity that can enter the body through contaminated food chains, so wastewater containing cadmium needs to be treated before being discharged into the environment. This study uses adsorption methods to reduce Cd(II) concentration in artificial wastewater by utilizing modified sengon wood sawdust cellulose as a bioadsorbent. Adsorption tests were conducted in batch mode at room temperature with constant stirring, and the results were analyzed using AAS. The objective of this study was to determine the optimum adsorption conditions using Response Surface Methodology (RSM) and to determine the adsorption capacity of the modified bioadsorbent based on the Freundlich or Langmuir adsorption isotherm models. The variations in bioadsorbent dose in this study were 2, 4, and 6 g/L; adsorption time variations were 30, 60, and 90 minutes; pH variations were 3, 4, and 5. Based on the design expert 13 RSM software, the optimum adsorption conditions for citric acid-modified bioadsorbent are a bioadsorbent dose of 3.957 g/L, time of 31.655 minutes, and pH of 4.968. For the EDTA-modified bioadsorbent, the optimum conditions were a bioadsorbent dose of 3.836 g/L, time of 30 minutes, and pH of 4.708. The results of the adsorption isotherm modeling indicate that the citric acid-modified and EDTA-modified bioadsorbents are more suitable for the Freundlich isotherm model due to their higher determination coefficient (R²). Thus, the adsorption capacities for the citric acid-modified and EDTA-modified bioadsorbents were determined to be 1.7828 mg/g and 1.5776 mg/g, respectively.